Seizure-associated central apnea in a rat model: Evidence for resetting the respiratory rhythm and activation of the diving reflex - S.M. Villiere; K. Nakase; R. Kollmar; J. Silverman; K. Sundaram; M. Stewart (Neurobiology of Disease, 2017)
Respiratory derangements, including irregular, tachypnic breathing and central or obstructive apnea can be consequences of seizure activity in epilepsy patients and animal models. Periods of seizure-associated central apnea, defined as periods >1 s with rapid onset and offset of no airflow during plethysmography, suggest that seizures spread to brainstem respiratory regions to disrupt breathing.We sought to characterize seizure-associated central apneic episodes as an indicator of seizure impact on the respiratory rhythm in rats anesthetized with urethane and given parenteral kainic acid to induce recurring seizures. We measured central apneic period onsets and offsets to determine if onset-offset relations were a consequence of 1) a reset of the respiratory rhythm, 2) a transient pausing of the respiratory rhythm, resuming from the pause point at the end of the apneic period, 3) a transient suppression of respiratory behavior with apnea offset predicted by a continuation of the breathing pattern preceding apnea, or 4) a random re-entry into the respiratory cycle.Animals were monitored with continuous ECG, EEG, and plethysmography. One hundred ninety central apnea episodes (1.04 to 36.18 s, mean: 3.2 ± 3.7 s) were recorded during seizure activity from 7 rats with multiple apneic episodes. The majority of apneic period onsets occurred during expiration (125/161 apneic episodes, 78%). In either expiration or inspiration, apneic onsets tended to occur late in the cycle, i.e. between the time of the peak and end of expiration (82/125, 66%) or inspiration (34/36, 94%). Apneic period offsets were more uniformly distributed between early and late expiration (27%, 34%) and inspiration (16%, 23%). Differences between the respiratory phase at the onset of apnea and the corresponding offset phase varied widely, even within individual animals.Each central apneic episode was associated with a high frequency event in EEG or ECG records at onset. High frequency events that were not associated with flatline plethysmographs revealed a constant plethysmograph pattern within each animal, suggesting a clear reset of the respiratory rhythm. The respiratory rhythm became highly variable after about 1 s, however, accounting for the unpredictability of the offset phase. The dissociation of respiratory rhythm reset from the cessation of airflow also suggested that central apneic periods involved activation of brainstem regions serving the diving reflex to eliminate the expression of respiratory movements. This conclusion was supported by the decreased heart rate as a function of apnea duration.We conclude that seizure-associated central apnea episodes are associated with 1) a reset of the respiratory rhythm, and 2) activation of brainstem regions serving the diving reflex to suppress respiratory behavior. The significance of these conclusions is that these details of seizure impact on brainstem circuitry represent metrics for assessing seizure spread and potentially subclassifying seizure patterns.